Incredible Years® Parent, Teachers and Children's Series: Transportability to Portugal of Early Intervention Programs for Preventing Conduct Problems and Promoting Social and Emotional Competence - Carolyn Webster-Stratton (Psychosocial Intervention, 2012)
Disruptive behavior disorders in children are on the increase. However, there is evidence that the younger a child is at the time of intervention, the more positive the behavioral effects on his/her adjustment at home and at school. Parental education might be an effective way of addressing early problems. The Incredible Years (IY) programs were designed to prevent and treat behavior problems when they first appear (in infancy-toddlerhood through middle childhood) and to intervene in multiple areas through parent, teacher, and child training. This paper summarizes the literature demonstrating the impact of the IY parent, teacher and child intervention programs, and describes in more detail the work done in Portugal so far to disseminate IY programs with fidelity, with particular emphasis on the IY Basic Preschool Parenting and Teacher Classroom Management programs.